Spatial Differentiation of Outstanding Financial Liabilities of Natural Persons in Poland - Nowak, Paweł (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2019)
The aim of the article is to present the degree of indebtedness of Poles in spatial terms and to explain the causes of this phenomenon. The conclusions from the analysis show that the overdue debt is the result of a combination of causes, two of which seem to be essential - these are economic (structural) and cultural reasons. Economic reasons relate mainly to a large number of state-owned farms in Western and Northern Poland in the period before 1989. On the other hand, cultural causes are related to the first and also relate to the issue of connection with the place of residence and ownership. The inhabitants of Western Poland constitute an immigrant population, poorly emotionally and legally bound with the place of residence. The opposite are the inhabitants of Eastern Poland, who are often associated with the same place for generations. Aspirations affecting the financial behaviour of the population, shaped by neighbouring countries, are not without significance. Rich Germany creates other (higher) consumption standards in the West of Poland, rather than poor Ukraine in the East. The article uses causal relationships and elements of historical analysis. The information in it comes from scientific studies and reports on overdue debt in 2007-2017. Due to the complexity of the issues undertaken, the findings in the article are mainly of a directional nature and constitute a starting point for further in-depth research.